Strategi Promosi Spa Reception Terhadap Produk Spa - Suridiasih, Ida Ayu Lakshmi; Adi, Ida Ayu Sri Puspa; Pitanapri, Made Uttari (Journal of Tourism and Hospitality Analysis (JoTHA), 2024)
This research aims to identify suitable promotional strategies for spa products at Spa X in Hotel X due to an imbalance in the number of guests visiting the spa. The research method involves primary data from interviews and documentary studies analyzed qualitatively. The research findings indicate a guest visit imbalance, particularly in the aspect of personal selling. Spa X never conducts business trips, spa reception staff do not promote on their personal social media, do not implement sales calls, and one staff member tends to upsell more than others. In terms of advertising, Spa X only uses the website and social media. Although sales promotions are reasonably good, there is a need to enhance offerings, such as special room packages for honeymoon or anniversary guests. Direct marketing is effective, but there is an issue with social media management that confuses guests. There are no plans for social activities that could impact the spa and hotel's image in the community. Therefore, Spa at X needs to implement more effective promotional strategies to increase the number of visiting guests.